2022
DOI: 10.3233/jifs-211217
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Bitcoin price using time opinion mining and bi-directional GRU

Abstract: Bitcoin is an innovative decentralized digital currency without intermediaries. Bitcoin price prediction is a demanding need in the present situation. This paper makes an investigation on the Bitcoin price forecast with a Bi-directional Gated Recurrent Unit (GRU) time series method, combined with opinion mining based on Twitter and Reddit feeds. An hourly basis sentimental analysis through the implementation of Natural Language Processing presents a positive impact of sentimental analysis on the Bitcoin price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Then deep learning and BLS develop from external neural networks. The classical deep learning methods for the time series prediction are GRU [23], LSTM [24], DeepESN [25], graph neural network [26], Fusion network [27], etc. LSTM belongs to the RNN network [28] and mainly solves the problem of gradient disappearance and explosion in RNN [29].…”
Section: Related Work 21 Time Series Prediction Methodsmentioning
confidence: 99%
“…Then deep learning and BLS develop from external neural networks. The classical deep learning methods for the time series prediction are GRU [23], LSTM [24], DeepESN [25], graph neural network [26], Fusion network [27], etc. LSTM belongs to the RNN network [28] and mainly solves the problem of gradient disappearance and explosion in RNN [29].…”
Section: Related Work 21 Time Series Prediction Methodsmentioning
confidence: 99%
“…The model was trained by deleting different input features each time, and the impact of each input feature on model performance and prediction accuracy was analyzed [6] . Begum SA and other scholars used GRU networks to predict stocks, and found that the bidirectional GRU model performed better by comparing unidirectional GRU [7] .…”
Section: Introductionmentioning
confidence: 98%